Epidemiological history and genomic characterization of non-D1 HBV strains identified in Iran (2015)
Background: Hepatitis B virus (HBV) has been classified into eight genotypes and forty subgenotypes. Genotype D of HBV is the most worldwide distributed genotype and HBV subgenotype D1 has been isolated from Iranian patients. Objective: To characterize for the first time complete genomes of recently emerged non-D1 strains in Iran. Study design: HBV complete genomes isolated from 9 Iranian HBV carriers were sequenced. Different diversities of the ORFs were mapped and evolutionary history relationships were investigated. Results: Phylogenetic analysis identified four D2 subgenotypes and five D3 subgenotypes of HBV in the studied patients. Of note, D2 strains clustered with strains from Lebanon and Syria. The time of the most recent common ancestor (TMRCA) of the first cluster of D2 was dated at 1953 (BCI. = 1926, 1976) while the second cluster was dated at 1947 (BCI. = 1911, 1978). All five Iranian D3 strains formed a monophyletic cluster with Indian strain and dated back to 1967 (BCI. = 1946, 1987). Surprisingly, two D3 strains had an adw2 subtype. Interestingly, more than 80% of the present strains showed precore mutations, while two isolates carried basal core promoter variation. Conclusion: Iranian D2 and D3 isolates were introduced on at least two and one occasion in Iran and diverged from west and south Asian HBV strains, respectively. Considering the impact of the different (sub) genotypes on clinical outcome, exploring the distinct mutational patterns of Iranian D1 and non-D1 strains is of clinical importance. © 2014 Elsevier B.V.